The Puzzle of Translation Skills. Towards an Integration of E-Learning and Special Concepts of Computational Linguistics into the Training of Future Translators - Jekat, Susanne J. J.; Massey, Gary (Linguistik Online, 2003)
The objective of this paper is to promote new methods in the computational training of translation students. We will show that the process of translation is more complex than often supposed but can be successfully supported by electronic tools. The acquisition of advanced skills in the combination of these fields is facilitated by the use of new teaching methods like e-learning and the introduction of special concepts in Computational Linguistics such as evaluation.